The The behavior of infants before hearing a lullaby (Scientific Journal of Eduardo Mondlane University, Serie: Educational Sciences, 2014)
The literature on lullabies shows, firstly, that this kind vocal comes in different parts of the world as a song bound to infancy; and secondly that the baby exhibits different behaviors when listening to a lullaby. In this article I will go and center myself in the study of lullaby addressing some features that make it a musical genre with specific purposes. Describe studies that reflect how the hearing lullabies influence the behavior of the baby during periods of sleep. From a case study for me, with babies from 4 to 6 months of age, I observed how hearing a lullaby influenced their behavior, during sleep. One conclusion of the study indicates that hearing the lullaby induces quiescence and subsequent sleep of infants and their well being.
Keywords: lullaby; music features; sleep; sing; hearing; behavior